Ben Sira's View of Women A Literary Analysis - Trenchard, Warren C. (Brown Judaic Studies, 2020)
This volume systematically analyzes all the material concerning women in Sirach, providing detailed exegesis in each case. It synthesizes this evidence to offer a fuller understanding of Ben Sira's perception of women.